Natural Deep Eutectic Solvents as Green Alternatives for Extracting Bioactive Compounds from Sideritis Taxa with Potential Cosmetic Applications - Lamprini Zissi; Virginia D. Dimaki; Vassiliki S. Birba; Vassiliki C. Galani; Vassiliki Magafa; Sophia Hatziantoniou; Fotini N. Lamari (Antioxidants)
This study investigated the potential of natural deep eutectic solvents (NADESs) for extracting bioactive compounds from the aerial parts of two mountain tea taxa, Sideritis clandestina ssp. peloponnesiaca (Boiss. & Heldr.) Baden and Sideritis raeseri Boiss. & Heldr. ssp. raeseri. Five NADEs, composed of betaine, glycerol, glucose, urea, citric acid, and sucrose, were evaluated for their extraction efficiency compared to conventional solvents (water and 70% ethanol). The total phenolic content (TPC) and antioxidant activity (FRAP and DPPH assays) were determined. Results showed that water was not a good extraction solvent. Despite the great solvent-dependent differences, most NADEs, particularly the betaine–glycerol–glucose mixture (BGG4), exhibited comparable or even superior extraction efficiency and antioxidant activity compared to 70% ethanol. The secondary metabolites in the BGG4 and 70% ethanol extracts were determined with HPLC-MS. The BGG4 extracts of both Sideritis taxa had a rich phenolic profile, with the major ingredients being chlorogenic acid, verbascoside, and non-, mono- and di-acetylated allosyl hypolaetin glycosides. Although distinct quantitative differences in their composition compared to the respective 70% ethanol extracts, and between them were noted, overall, the content of secondary metabolites in both S. raeseri extracts was lower than that of the S. clandestina extracts. These findings suggest that NADEs, particularly BGG4, are promising green solvents for extracting bioactive compounds from Sideritis taxa, paving the way for potential applications in the development of natural and sustainable cosmetic products.